Puritanism and Liberty Revisited: The Case for Toleration in the English Revolution - Coffey, John (The historical journal, 1998)
In recent years historians have grown sceptical about attempts to trace connections between puritanism and liberty. Puritans, we are told, sought a godly society, not a pluralistic one. The new emphasis has been salutary, but it obscures the fact that a minority of zealous Protestants argued forcefully for the toleration of heresy, blasphemy, Catholicism, non-Christian religions, and even atheism. During the English revolution, a substantial number of Baptists, radical Independents, and Levellers insisted that the New Testament paradigm required the church to be a purely voluntary, non-coercive community in the midst of a pluralistic society governed by a ‘merely civil’ state. Although their position was not without its ambiguities, it constituted a startling break with the Constantinian assumptions of magisterial Protestantism.